Impact of Bariatric Surgery on Cardiovascular Outcomes in Obese Patients: A Systematic Review and Meta-Analysis - Muhammad Twaha Zia, Waniya badar khan, Zarhaish Barkat-Ullah, Zainab Dilshad, Maham Dilshad (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Background: Obesity is a major risk factor for cardiovascular diseases (CVDs), which remain the leading cause of global morbidity and mortality. Bariatric surgery offers sustained weight loss and potential cardiovascular benefits beyond conventional treatments. Objective: To evaluate the effect of bariatric surgery on cardiovascular outcomes in obese patients through a systematic review and meta-analysis. Methods: A systematic literature search was conducted across PubMed and Google Scholar for studies published up to July 2025. Screening was performed using Rayyan software, and eligible randomized controlled trials and cohort studies comparing cardiovascular outcomes in bariatric surgery versus non-surgical obese patients were included. Data from 14 studies encompassing over 759,000 participants were extracted and analyzed. Meta-analyses were performed using RevMan software with random-effects models to calculate pooled risk ratios and assess heterogeneity. Results: Bariatric surgery significantly reduced risks of ischemic heart disease (RR=0.58), heart failure (RR=0.62), MACCE (RR=0.66), revascularization (RR=0.44), cerebrovascular events (RR=0.73), and all-cause mortality (RR=0.36). Non-significant trends were seen for myocardial infarction and cardiac death. Conclusions: Bariatric surgery significantly lowers several major cardiovascular risks and mortality in obese patients, supporting its role in cardiovascular risk management. Keywords: Bariatric Surgery; Cardiovascular Diseases; Obesity; Meta-Analysis; Treatment Outcome